The distribution of top incomes in former British West Africa 1 - (:unkn) unknown (My University, 2020)
This paper explores what can be learned about the upper tail of the income distribution in the British West African colonial territories, exploiting the administrative statistics on the operation of the colonial personal income tax. These statistics covering the middle of the twentieth century have definite limitations, but then little is known about the distribution of income in the colonies at that time. In historical studies of the development of the economy of Ghana (previously the Gold Coast), for example, the absence of adequate data is a constant theme: “poor statistics conspire to prevent even the roughest estimates of the overall distribution of the national income” (Killick, 1978, page 80) or “data on income distribution in Ghana are not readily available” (Huq, 1989, page 56).Writing about four countries, including Ghana and Nigeria, Phillips (later Commissioner of the Ministry of Finance in Ogun State in Nigeria), concluded that “studies of income distribution in these countries have been thin on the ground; in the few analyses that exist, size distribution has received very scant attention … in most respects, long time-series data are hard to come by” (1975, page 1).
Keywords: African Research